Psychosocial effects of Corona virus measures on (pre‐)dementia patients during 2nd lockdown. (December 2021) - Bakker, Els D; Van Maurik, Ingrid S; Mank, Arenda; Zwan, Marissa D; van den Buuse, Susanne; van den Broeke, Jennifer R; Gillissen, Freek; van de Beek, Marleen; Lemstra, Evelien; van den Bosch, Karlijn A; van Leeuwenstijn, Mardou; Bouwman, Femke H; et al.
Abstract: Background: The COVID‐19 pandemic poses enormous social challenges, especially during lockdown. Recently, the second lockdown started in the Netherlands. We aimed to investigate and compare the psychosocial effects of corona measures during lockdown in memory clinic (pre‐)dementia patients and their caregivers. Method: During second lockdown, n=137 symptomatic patients (age=67.7±6.54, 36.5%F, MMSE = 24.4±4.7; n=82 dementia, n=55 MCI), n=244 cognitively normal (age=63.6±7.56, 38.9%F, MMSE = 28.8±1.18; SCD) and n=198 caregivers of Alzheimer Center Amsterdam completed a survey on psychosocial effects of corona. Questions related to loneliness, worries for faster cognitive decline, psychological and behavioral problems. In a subset of patients (n=169) and caregivers (n=38) we were able to compare their answers to answers on a similar survey completed during first lockdown (May 2020). Result: In total, n=17 (4.5%) patients [n=3 (2.2%) symptomatic, n=14 (5.7%) cognitively normal] and n=8 (4%) caregivers reported a positive test result for COVID‐19. Over one‐third of caregivers reported worries for faster cognitive decline [n=76 (38%)] and behavioral problems [n=70 (35%)] in patients. Feelings of loneliness were experienced by n=23 (17%) symptomatic patients, n=44 (18%) cognitively normal and n=50 (25%) caregivers. One quarter of patients [n=78 (25%)] reported more depressive feelings during lockdown [n=27 (20%) symptomatic, n=51 (21%) cognitively normal]. More feelings of fatigue were reported by n=23 (17%) symptomatic patients, n=46 (19%) cognitively normal, and n=67 (34%) caregivers. Comparing results to those obtained during the first lockdown, feelings of loneliness [Χ 2 =26.4, p<.001 in patients, Χ 2 =10.3, p<.001 in caregivers] and anxiety [Χ 2 =25.9, p<.001 in patients, Χ 2 =6.69, p=.010 in caregivers] increased. During second lockdown, less feelings of apathy [Χ 2 =13.0, p<.001], but more depressive feelings [Χ 2 =27.6, p<.001] were reported in patients compared to first lockdown. Caregivers were more worried for memory decline in patients during second lockdown [Χ 2 =4.09, p=.043]. Conclusion: Compared to first lockdown, feelings of loneliness, anxiety, worries for faster cognitive decline and depressive feelings increased in second lockdown. A noticeable part of (pre‐)dementia patients and caregivers report feelings of loneliness, worries for faster cognitive decline, psychological and behavioral problems in second lockdown. These psychosocial effects are more frequently reported by caregivers than patients.